Effect of positive end-expiratory pressure on functional residual capacity in two experimental models of acute respiratory distress syndrome. Issue 6 (June 2020) - Wang, Yu-Mei; Sun, Xiu-Mei; Zhou, Yi-Min; Chen, Jing-Ran; Cheng, Kun-Ming; Li, Hong-Liang; Yang, Yan-Lin; Zhou, Jian-Xin
Objective: Measurement of positive end-expiratory pressure (PEEP)-induced recruitment lung volume using passive spirometry is based on the assumption that the functional residual capacity (FRC) is not modified by the PEEP changes. We aimed to investigate the influence of PEEP on FRC in different models of acute respiratory distress syndrome (ARDS). Methods: A randomized crossover study was performed in 12 pigs. Pulmonary (n = 6) and extra-pulmonary (n = 6) ARDS models were established using an alveolar instillation of hydrochloric acid and a right atrium injection of oleic acid, respectively. Low (5 cmH2 O) and high (15 cmH2 O) PEEP were randomly applied in each animal. FRC and recruitment volume were determined using the nitrogen wash-in/wash-out technique and release maneuver. Results: FRC was not significantly different between the two PEEP levels in either pulmonary ARDS (299 ± 92 mL and 309 ± 130 mL at 5 and 15 cmH2 O, respectively) or extra-pulmonary ARDS (305 ± 143 mL and 328 ± 197 mL at 5 and 15 cmH2 O, respectively). The recruitment volume was not significantly different between the two models (pulmonary, 341 ± 100 mL; extra-pulmonary, 351 ± 170 mL). Conclusions: PEEP did not influence FRC in either the pulmonary or extra-pulmonary ARDS pig model.